2021
DOI: 10.1101/2021.06.01.446616
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Building Back More Equitable STEM Education: Teach Science by Engaging Students in Doing Science

Abstract: The COVID-19 pandemic is a national tragedy, one that has focused our attention on both the need to improve science education and the need to confront systemic racism in our country. We know that active learning strategies, in particular research experiences, can engage and empower STEM undergraduates, effectively closing the achievement gap for historically excluded persons. The apprenticeship model for STEM training - supervised research under a dedicated mentor - is highly effective, but out of reach for mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The National Science Foundation (USA) acknowledges that "scientific merit is intertwined with broader impacts" and that "educational reforms must now center inclusion and equity" Elgin et al (2021, p. 7). It is argued that the COVID-19 pandemic showed that academia has a responsibility to decrease structural inequities in education whereby one strategy could be to engage STEM students in research (Elgin et al 2021). At the same time, it is noted that problems exist in STEM education (Garibay 2015;Josa and Aguado 2021).…”
Section: Engineering Educationmentioning
confidence: 99%
“…The National Science Foundation (USA) acknowledges that "scientific merit is intertwined with broader impacts" and that "educational reforms must now center inclusion and equity" Elgin et al (2021, p. 7). It is argued that the COVID-19 pandemic showed that academia has a responsibility to decrease structural inequities in education whereby one strategy could be to engage STEM students in research (Elgin et al 2021). At the same time, it is noted that problems exist in STEM education (Garibay 2015;Josa and Aguado 2021).…”
Section: Engineering Educationmentioning
confidence: 99%
“…Course-based undergraduate research experiences (CUREs) bring students directly to authentic research with their peers in a classroom setting and are defined by use of scientific practices, discovery, relevant and/or important work, collaboration, and iteration ( Auchincloss et al 2014 ). Whereas government-focused programs (such as the NSF Research Experiences for Undergraduates [REU] program) traditionally offer limited laboratory space to a small number of students, CUREs expose a larger group of students in tandem ( Elgin et al 2021 ). CUREs break down student financial and personal barriers and can minimize faculty members’ unconscious bias ( Bangera and Brownell 2014 ).…”
Section: Engineer Multiple Student Pathwaysmentioning
confidence: 99%
“…Though CUREs have many benefits ( Elgin et al 2021 ), UI faculty sometimes receive pushback for implementing CUREs or requesting research classroom hours within established curricula. One solution is creating a variety of CUREs with flexible length/timing (weeks or semester long) in mind.…”
Section: Engineer Multiple Student Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations